2D mesoscale modeling of compressive fracture in concrete using a mesh fragmentation technique. (1st January 2023) - Gimenes, Marcela; Rodrigues, Eduardo A.; Bitencourt, Luís A.G.; Manzoli, Osvaldo L.
Abstract: The computational prediction of the failure processes of concrete under compression is still a challenge. Several researchers have proposed mesoscale models to have a better understanding of the influence of the distinct phases of the concrete on the fracture process. In this sense, this work proposes an extension of the mesoscale model proposed by Rodrigues et al. (2016) to describe the complex failure behavior of concrete under compression. In the proposed 2D approach, two layers of interface elements are inserted into the standard finite element mesh to define the potential crack paths using the mesh fragmentation technique. Each layer is formed by a pair of high aspect ratio elements and is responsible for modeling the tensile or frictional shear failure behavior. According to this approach, the compressive failure is a consequence of the combination between tensile and shear failure modes in the mesoscopic scale. The use of these two damage models allows to represent the debonding (opening) between the aggregates and matrix due to local tensile stress concentration, i.e. the fracture propagation in mode-I, as well as the sliding process corresponding to the fracture propagation in mode-II. Furthermore, adopting adequate parameters, these models allow representing the friction condition between the concrete specimen and the steel loading plates. The failure behavior of compression tests with different specimen slenderness as well as the different friction restraints between loading platen and concrete specimen is predicted. The numerical results are compared qualitatively and quantitatively against the experimental results found in the literature, demonstrating that the proposed approach is able to describe the failure process of concrete in compression. Highlights: An extension of the mesh fragmentation technique is proposed using a two-layer condensed interface element. Tensile and shear friction damage models are combined to represent the fracture processes of concrete under compression. The numerical results obtained are consistent with experimental tests of concrete under uniaxial and biaxial compression. The model allows the representation of different testing boundary conditions by means of a friction parameter. The numerical analysis shows that the compressive failure is not only function of the material property, but a combination of material and structural behaviors.